Upaya Meningkatkan Motivasi Belajar dengan Model PBL dan Pendekatan CRT Mata Pelajaran IPAS di Kelas 5 SDN 101766 Bandar Setia - Sitinjak, Feli Finna; Samio, Samio; Asnawi, Asnawi; Aldianu, Deri (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study is motivated by the low learning motivation of 5thgrade students at SD Negeri 101766 Bandar Setia in the subject of Natural and Social Sciences (IPAS), specifically on the digestive system material. Low motivation hinders the learning process and students’ competency achievement. The purpose of this research is to improve students’ learning motivation through the implementation of the Problem Based Learning (PBL) model combined with a Culturally Responsive Teaching (CRT) approach. This classroom action research (CAR) involved 25 fifthgrade students of SD Negeri 101766 Bandar Setia as subjects. Data were collected using observations, motivation questionnaires, and documentation, and analyzed descriptively. The results show a significant increase in students’ motivation from the preaction phase to the second cycle. Initially, only 12% of students had very high motivation and 20% had high motivation; by the second cycle, very high motivation rose to 56% and high motivation to 44%, while students with low and very low motivation were completely eliminated. The implementation of PBL combined with CRT proved effective in creating a more active, creative, and meaningful learning environment that aligns with students’ cultural contexts. This study recommends the continuous use of this learning model to enhance educational quality at SD Negeri 101766 Bandar Setia